An Anthropomorphic Head Phantom Prototype for the Measurement of Geometric Distortion in Magnetic Resonance Imaging System - sadegh shurche; Mohammad Yousefi sooteh (Iranian Journal of Medical Physics, 2024)
Introduction: Our goal is to design and construct a new anthropomorphic head phantom for assessment of image distortion in treatment planning systems. Material and Methods: In this study, CT scan images of heads were transferred to the Mimic software. Using this software, the skull texture was removed and a hollow layer was formed between the bone tissues, in which the bone tissue would be equivalent to the material. Then it was fabricated with a 3D printer using K2HPO4 (as bone). A new phantom containing 8,000 reference features (control points) with AutoCAD software designed, fabricated it with a 3D printer and filled it with gels that included nickel-doped agarose, urea, and sodium chloride (as soft tissue) and then placed this grid inside the head phantom. This phantom was tested on the Siemens 3 Tesla Prisma MRI model using a 64-channel head coil. In this regard, a three-dimensional reference model was used. Reproducibility on the phantom was investigated with three different imaging sessions per day for three different days. Results: T2 gel value, 84.804 ± 3ms was obtained for gel that simulates brain tissue. In addition, their corresponding T1 measurements were 1090.92 (ms), respectively. By Adding nickel to agarose gels, the amount of CT number in all energies of 80 to 130 kVp increased. Increasing the concentration of nickel in gels results in a decrease in CT number. The geometric distortion in the 3D results was found to be due to field non-uniformity and nonlinearity of the gradients and its reproducibility. Conclusion: The results show that, the amount of distortion in the middle of the field was less than that of its sides. This phantom can be used to check image distortion in treatment planning systems.